Zakat Fitrah kepada Dukun Bayi dalam Perspektif Hukum Islam - Hidayat, Moh Taufik; Handayani, Tri; Adzkiya, Ubbadul; Masruri, Ali (Universitas Wahid Hasyim Semarang, 2021)
The implementation of zakat fitrah is generally left to the amil zakat, so that the practice of zakat goes well according to the guidance of Islamic law, meaning that muzakki pays zakat really mustahik also receive according to conditions as a group that is entitled to receive zakat fitrah. The zakat fitrah manager in Lipursari Village, residents who have children under the age of 2 years, issue zakat directly to their dukun and not through the zakat fitrah manager (Amil) at the local mosque. The focus in this article is to describe the practice of distributing zakat fitrah to traditional birth attendants, how Islamic law views the practice of distributing zakat fitrah to traditional birth attendants, and the obstacles that occur in the distribution of zakat. The type of research carried out by researchers is field research or field research conducted in the village of Lipursari. The author uses data collection methods, namely interviews. Sources of data in this study are sourced from primary data and secondary data sources. Then the writer analyzed using descriptive analysis method using a qualitative approach. The results showed: The practice of Zakat Fitrah to traditional birth attendants in the village of Lipursari was not in accordance with the Zakat Law no. 23 of 2011. However, the distribution of zakat fitrah is allowed, it is because one of the customs that is running or carried out by the local community has existed for a long time and has been passed down from generation to generation. The traditional birth attendant in the village of Lipursari is included in the group of people who are entitled to receive zakat fitrah. This is because the people in Lipursasi village are mostly farmers, so the traditional birth attendants do not burden the local community to give large amounts of wages, because basically the traditional birth attendant has the principle of ta'awun or help for the common welfare.